2004
DOI: 10.1152/ajpgi.00275.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of leukocytes and platelets in mediating hepatocyte apoptosis in a rat model of systemic endotoxemia

Abstract: Apoptotic hepatocytes have been demonstrated to represent an important signal for transmigration of leukocytes sequestered in sinusoids during endotoxemia in vivo. Beside leukocytes, platelets and their adhesion to endothelial cells and leukocytes have been implicated in inflammatory liver injury. Using in vivo multifluorescence microscopy, we examined the possibility that hepatocellular apoptosis causes both leukocytes and platelets to colocalize within the sinusoidal microvasculature of endotoxemic livers. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 37 publications
7
86
0
3
Order By: Relevance
“…16 Microcirculatory disturbances and liver injury have been shown to be interrelated in animal studies and human studies in the setting of ischemia reperfusion, endotoxin-induced liver injury, or druginduced liver injury. [17][18][19][20] Accordingly, in the current study, LDH efflux from isolated perfused livers increased to a higher degree in cholestatic livers than in sham-operated livers following KC activation. The good correlation between LDH efflux and transaminases has been shown in different earlier studies.…”
Section: Discussionsupporting
confidence: 49%
“…16 Microcirculatory disturbances and liver injury have been shown to be interrelated in animal studies and human studies in the setting of ischemia reperfusion, endotoxin-induced liver injury, or druginduced liver injury. [17][18][19][20] Accordingly, in the current study, LDH efflux from isolated perfused livers increased to a higher degree in cholestatic livers than in sham-operated livers following KC activation. The good correlation between LDH efflux and transaminases has been shown in different earlier studies.…”
Section: Discussionsupporting
confidence: 49%
“…Liver cell apoptosis represents not only a crucial step in acute hepatic failure, but also functions as a signal for leukocyte infiltration in parenchymal cells, 29,30 thereby establishing a vicious circle with the augmentation of leukocyte inflammation and cell death, although necrosis is also likely to markedly contribute to the liver injury in view of the elevation of serum liver transaminase levels and histological findings (see Leonis et al 25 and Figures 1 and 4 in this study). Consistent with this, preventing apoptosis in hepatocytes by caspase inhibition reportedly suppresses leukocyte transmigration and leukocyte-dependent liver cell necrosis accompanied by apoptosis.…”
Section: Uti In Liver Injury With Coagulatory Disturbancementioning
confidence: 75%
“…Using a Zeiss fluorescence microscope equipped with a 100 W mercury lamp and different filter sets for blue, green, and UV epi-illumination (Axiotech Vario; Zeiss, Jena, Germany), microscopic images were taken by water immersion objectives (ϫ20/0.50W, ϫ40/0.8W; Zeiss), televised using a charge-coupled device video camera (FK 6990A-IQ; Pieper, Berlin, Germany), and recorded on videotape for subsequent off-line evaluation. 9 Blood perfusion within individual sinusoids was studied after tissue contrast enhancement by sodium fluorescein (2 mol/kg body weight i.v. ; Merck, Darmstadt, Germany) and blue light epi-illumination (450 to 490/Ͼ520 nm, excitation/emission wavelength).…”
Section: Intravital Fluorescence Microscopymentioning
confidence: 99%
“…6 Within the extremely complex cascade of pathophysiological events, representing the systemic inflammatory response, great attention has recently been brought to the contribution of apoptosis in organ dysfunction and failure. 7,8 Hepatocellular apoptosis represents not only a crucial step in ALF but functions also as a signal for leukocyte migration and attack on parenchymal cells, 9,10 thereby establishing a vicious circle with aggravation of leukocytic inflammation and final cell death. It has been shown that preventing apoptosis in hepatocytes by caspase inhibition suppresses leukocyte transmigration and leukocyte-dependent liver cell necrosis.…”
mentioning
confidence: 99%